Mesoporous NiCu-CeO2 oxide catalysts for high-temperature water-gas shift reaction - Jha, Ajay; Jeong, Dae-Woon; Jang, Won-Jun; Rode, Chandrashekhar V.; Roh, Hyun-Seog (RSC Advances, 2015)
Mesoporous NiCu-CeO2 oxide catalysts were synthesized by using the evaporation-induced self-assembly method applied to the high-temperature, water-gas shift reaction (HT-WGS) between 350 to 550 degrees C. Nickel and copper loadings on mesoporous ceria were tailored to achieve high activity and selectivity by suppressing methane formation in HT-WGS. Among the prepared catalysts, NiCu(1 : 4)-CeO2 exhibited the highest selectivity to CO2 and H-2 with 85% CO conversion at a very high GHSV of 83 665 h(-1). The higher activity of the catalysts was due to the mesoporous architecture, which provides more accessible active sites for the WGS reaction. Powder X-ray diffraction (XRD), small angle X-ray scattering (SAXS), N-2-adsorption/desorption isotherm, high-resolution transmission electron microscopy (HR-TEM), and H-2-temperature-programmed reduction (TPR) techniques were used to understand the role of mesoporosity and bimetallic composition of various NiCu-CeO2 oxides in enhancing catalytic activity for HT-WGS.